2012
DOI: 10.1007/s00125-012-2770-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of day and fasting duration on measures of glycaemia: analysis from the Whitehall II Study

Abstract: Aims/hypothesis We aimed to study diurnal variation in glucose regulation by examining the effects of time of day and fasting duration on fasting plasma glucose (FPG), 2 h post-load plasma glucose (2hPG) and HbA 1c levels. Methods We analysed data from 5,978 non-diabetic white men and women from the prospective Whitehall II Study. All studied participants fasted for at least 8 h before a clinical examination, which included an OGTT and anthropometric measurements. We fitted mixed-effects models for FPG, 2hPG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
2
14
2
2
Order By: Relevance
“…The literature explains that unlike HbA1c, blood glucose levels are influenced by external factors, such as caloric intake and fasting. 30,31 However, further analysis and research is needed to clarify the herein results.…”
Section: Discussioncontrasting
confidence: 46%
“…The literature explains that unlike HbA1c, blood glucose levels are influenced by external factors, such as caloric intake and fasting. 30,31 However, further analysis and research is needed to clarify the herein results.…”
Section: Discussioncontrasting
confidence: 46%
“…The participants were instructed to fast for 8 h prior to the health examinations, and therefore our data do not capture night‐time eating. We used the HbA 1c criteria for prediabetes/diabetes, because fasting and 2‐h plasma glucose are affected by the time of day and fasting duration prior to blood sampling . Accordingly, these measures would not be independent of the TLEE prior to the examination.…”
Section: Discussionmentioning
confidence: 99%
“…Convention-ally, it is believed that fasting duration is not important for performing 50 g GCTs, and many institutions recommend the test to be performed without restrictions on eating or drinking. Some studies have suggested that fasting duration influences the glucose level following a 50 g GCT in pregnant women [7,9,15], and that this duration (1-2 h, > 2 h) at different times of the day (morning, afternoon, or night) influences the test results [12]. Reportedly, this situation is associated with the increased secretion of insulin in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…However, an abnormal 50 g GCT result does not always indicate GDM. Reportedly, fasting duration (the time since the last caloric intake) may have an effect on the plasma glucose level in pregnant women, and it may influence the gestational GCT results [7][8][9].…”
Section: Introductionmentioning
confidence: 99%